PENDAPATAN KELUARGA DAN ASUPAN ZAT GIZI MIKRO DENGAN KEJADIAN STUNTING PADA ANAK USIA 6-24 BULAN DI KELURAHAN LANDASAN ULIN UTARA: Family Income And Intake Of Micronutrients With Stunting Incidence InChildren Aged 6-24 Months In North LandasanUlin Village - Halidah; Yudistira, Sigit; Suryani, Nany; Solechah, Siti Aisyah (Jurnal Pangan Kesehatan dan Gizi Universitas Binawan, 2023)
Stunting is a chronic condition that describes stunted growth due to long-term malnutrition. Stunting is defined as a length for age Z score (LAZ) less than -2 SD. This study aimed to analyze the relation of family income and intake of micronutrients to the incidence of stunting in children under two years in North Landasan Ulin Village. This analytic observational study used a case control design. The research samples were 26 children under two years in the case group (stunting) and 26 children under two year in the control group (not stunted) taken using a purposive sampling technique. Length data were measured using an infantometer, family income was assessed through interviews and questionnaires, intake of micronutrients were collected using a 3x24 hour food recall. Data were analyzed using the Spearman Rank test. The results of this study indicated that family income (p=0.155) and intake of vitamin A (p=0.182) were not associated with the incidence of stunting in children under two years, whereas intake of iron (p=0.001) and zinc (p=0.001) were associated with the incidence of stunting in children under two years. Stunting can be prevented with sufficient intake of iron and zinc as needed, and the allocation of family income and vitamin A must also be considered. Keywords: Family income, iron, stunting, vitamin A, zinc